2018
DOI: 10.1097/md.0000000000011832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose intravenous dexamethasone on subjective voice quality after thyroidectomy

Abstract: Background:Corticosteroids are widely used to treat voice change after thyroidectomy. In this study, we evaluated the effect of a single dose of intravenous dexamethasone after thyroidectomy using a metaanalysis.Methods:Relevant studies were identified by searching the following databases: Medline, Embase, and Cochrane through February 2017. We followed PRISMA guidelines. The following search terms were used: “thyroidectomy,” “voice,” “steroid.” Random-effects models were used to estimate standardized mean dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cheng in 2015 compared four studies (one observational and three controlled randomized) about the use of steroids immediately after induction of anesthesia, concluding that these studies failed to demonstrate any clinical benefit in thyroid surgery [27]. On the other hand, Kim, lately in 2018, with his meta-analysis evaluating the same four studies concluded that dexamethasone' use before surgery may impacts positively outcomes, but further studies were required to corroborate their findings [26]. Two more papers in the current literature tried to answer the question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng in 2015 compared four studies (one observational and three controlled randomized) about the use of steroids immediately after induction of anesthesia, concluding that these studies failed to demonstrate any clinical benefit in thyroid surgery [27]. On the other hand, Kim, lately in 2018, with his meta-analysis evaluating the same four studies concluded that dexamethasone' use before surgery may impacts positively outcomes, but further studies were required to corroborate their findings [26]. Two more papers in the current literature tried to answer the question.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids are often used in orthopedic surgery and neurosurgery to reduce edema and neural dysfunction associated to surgical traumatism [21][22][23]. In thyroid surgery, usually dexamethasone is used by anesthesiologists to manage postoperative nausea and vomiting with scant reports, sometimes contradictory, about their role in ameliorating postoperative voice quality or preventing postoperative vocal cord palsy [24][25][26][27][28]. In this paper, we evaluate the impact of an early single injection of 4 mg dexamethasone at the time of a LOS during neuromonitored thyroidectomy, with regard of EMG signal recovery and changing of intraoperative strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy was enhanced with higher doses of dexamethasone (8–10 mg) and when given before induction of anesthesia, as the onset of action is 1 to 2 hours following administration 223. In addition, the use of perioperative or intraoperative steroids may reduce the rate of voice dysfunction and recovery time of recurrent laryngeal nerve palsy 221,224–229 Recommendation 5-16: Before PTX, in the absence of contraindications, a single preoperative dose of dexamethasone should be considered to reduce nausea, vomiting, and pain.…”
Section: Preoperative and Perioperative Carementioning
confidence: 99%
“…223 In addition, the use of perioperative or intraoperative steroids may reduce the rate of voice dysfunction and recovery time of recurrent laryngeal nerve palsy. 221,[224][225][226][227][228][229] Recommendation 5-16: Before PTX, in the absence of contraindications, a single preoperative dose of dexamethasone should be considered to reduce nausea, vomiting, and pain. (Strong recommendation, highquality evidence.…”
Section: Steroidsmentioning
confidence: 99%
“…Although there was no consensus regarding their effect on postoperative voice quality, however, these studies showed that steroid administration effectively reduces pain, nausea, and vomiting after surgery. The recent meta-analyses concluded that there was insufficient evidence to claim perioperative systemic steroids' effect on improving voice outcomes after thyroid surgery [89][90][91]. The EBSLN, a branch of the vagus nerve, is the motor nerve to the cricothyroid muscle, an essential tensor of the vocal folds.…”
Section: Wang Et Al Analyzed the Benefits Of Intraoperative Corticosteroids For Reducing Rln Palsymentioning
confidence: 99%